Proyecto de factibilidad para la creación de una empresa productora de suelas de zapatos, y su comercialización en la ciudad de Quito - Medrano Chamorro, Ney Giovanny (2015)
The soles ofthe shoeis a product ofgreat successwithin the guildof shoemakers, which is whythisstudy was toDETERMINE THE FEASIBILITYOVERALL OBJECTIVETO CREATEA COMPANY PRODUCINGSHOE SOLES,AND MARKETINGIN THE CITY OFQUITO,which will haveappropriateprocessesthat ensure ahigh quality productto reachquality standardsset bythe industry. Thiswork primarilycontains bibliographicbackupsfor the practical developmentof the different studiesof the thesis.Likewisematerials andmethods, the samethat servedthat facilitatedthe process andpresentation of resultsinvolvedin the different studiesare presented. The methods usedscientific, inductive, deductive, analytical methodis; techniquesapplied werethesurvey. Forthe market study353were appliedto a sampleof the population ofshoemakersQuitoaccording to datageneratedInternal Revenue Servicein 2015were3,005, as potentialplaintiffsProductand 18surveysbidders, total number of producers ofshoe soles(shoes) toQuitolevel, establishing thatfor the firstyearhas apotential demandof3,005shoemakers; 2284real demand forshoemakers andeffective demand for127.162soles, an offer of 9534 soles, stating that the project will have anunmet117628soles. The technical studythemacroandmicrolocation of the companywas raised,givenwill bein the city ofQuitoPichincha province, specifically in the MagdalenaneighborhoodstreetsCarlosPoitandFrancisco deVictoriadue tothe availability ofmeans and resources, mainlyaccessto raw materials. According to the resultsthe companyis able tooffer28800soles andfor the firstyear, acapacity utilizationof 80%will be takentooffer the product. In engineeringproject, the distribution of the plantwas determined, process flow, flow chartand technical(equipment,machinery)requirements, as well as furnitureand fixturesoffice, which is requiredfor normalwas designedperform their dutieswithin the company. In the organizationalandadministrative studythe organizational structure ofthe companyis described, legal and regulatoryfactors neededfor properimplementation ofthe companyin the countryare considered,it was established thatthe companyisa LimitedCompany, in addition to thus theorganicstructurewas implemented-functionallevelsformanagement, executive, legislative, advisory, operationalassistant, also a proposedmanualfunctionsas a basisfor implementingthe organizationof the companyis made.The companyshall haveonemanager, onecounsel, oneaccountantsecretary,oneproduction manager, 2 workers andonevendorpartnersthat will help thedevelopment of the companyandmeet thedemands of consumers. Inthe economic studycomprisedall investmentsin fixed assets,deferred assets, working capitalfinancing andall financial statementsthat are required toensure the financialassessmentand identify whetherthe project is feasibleor not;obtainingthe required investmentis $28,833.15equityestimatedat 65% which is $18,833.15anddebt capitalcorresponds to 35% through a loantoBancode Fomentoof$ 10,000.00to 4 yearsterm. The financial evaluationproduced the following results: TheVAN, gives a value of47380.15is feasiblefor implementation. TheTIRis35.84%, which likewiseissatisfactory valuefor the project.The benefit-cost (RB /C) is $1.25,meaning thatfor every dollar investedwill havea recoveryof$ 0.25cents.Thecapital recoveryperiod(PRC) is 2 years, 3 monthsand 1 day, sensitivity valuesare0.99withrising costsand 0.99withlower revenues. Thechanges in costsand revenues, increased by 16.93%and13.54%decreasedinallowingshow that the projectis not sensitive tosuch changes. At workconsistconclusions andrecommendationswhichverified thatthe project is feasiblebythe data presented inthis part. Finallyconsistliteratureorcollectionof booksand authors of thetheories presentedin the thesisand annexeswherethe summary ofproyectoandsample surveysforthe supply and demandof theproduct